2020
DOI: 10.1371/journal.pone.0226773
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle index and its association with hypertension among community adults in Sri Lanka: A cross-sectional study

Abstract: Objectives To investigate the association between a healthy lifestyle index (HLI) (i.e., a composite score comprising multiple lifestyle factors) and hypertension among community adults living in Sri Lanka. Methods The present study used baseline information of a cluster randomized controlled trial among 456 adults aged 27-65 years in a semi-urban community in Colombo, Sri Lanka. The HLI was constructed by summing a number of low-risk lifestyle factors: low body mass index, sufficient physical activity, non-sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The risk of hypertension and level of blood pressure increased with the unhealthful lifestyle. A Sri Lankan study found an inverse relationship between a healthy lifestyle index (low BMI, inadequate physical activity, non-smoking, low alcohol intake, and adequate intake of fruits and vegetables) and hypertension (38). In addition, a study in the middle-aged and older Australian population has indicated that the higher the number of risk lifestyle factors, the greater the OR for hypertension (39).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of hypertension and level of blood pressure increased with the unhealthful lifestyle. A Sri Lankan study found an inverse relationship between a healthy lifestyle index (low BMI, inadequate physical activity, non-smoking, low alcohol intake, and adequate intake of fruits and vegetables) and hypertension (38). In addition, a study in the middle-aged and older Australian population has indicated that the higher the number of risk lifestyle factors, the greater the OR for hypertension (39).…”
Section: Discussionmentioning
confidence: 99%
“…DM was defined as fasting plasma glucose of ≥7.0 mmol/L and/or self-reported history of hypoglycemic drug use [ 20 ]. The healthy lifestyle index was defined as the composition of five modifiable lifestyle factors, including BMI, physical activity, smoking status, drinking status, and fruit and vegetable consumption [ 21 ]. Regular exercise was defined as ≥150 minutes/week of moderate-intensity physical activity or ≥75 minutes of vigorous-intensity physical activity [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lifestyle factors (Quality of life). We were interested in measuring the impact of different lifestyle factors as a composite score that comprised multiple factors [19,20]. For these questions, face and content validity were calculated among the research group and three rounds of evaluation were performed per question by consensus.…”
Section: Escan-covid19mx Surveymentioning
confidence: 99%